The development of an early dyscalculia test - Wong, Ken Keong (2016)
Dyscalculia is a specific mathematics learning disability that affects the ability to acquire basic numeracy skill and is known as a deficit in numerosity. The primary cause of dyscalculia currently appears to be a genetically determined disorder of number sense. In an effort to raise awareness and understanding of dyscalculia among parents, teachers, and the general public, this thesis is the Design and Development research (DDR) and involved development of the Early Dyscalculia Test (EDT), a computer-based instrument for early diagnosis of dyscalculia. To ensure that the target students were relevant to learning disability in mathematics, students in Numeracy and Literacy Screening Programme (LINUS) were chosen as respondents. Due to the large and widely dispersed of the population of LINUS students in Sabah, the cluster sampling method was employed as the main sampling method in this study. As a result, the total sample size in this study consisted of 448 LINUS students. The study findings were analyzed by referring to the results obtained from the EDT and involving the analysis of data of Item Response Model (IRM), Microsoft Excel and Statistical Package for the Social Sciences (SPSS). Results of this study indicated that the instrument constructed from the numerosity concept and mathematical thinking framework provided valid and reliable measures of dyscalculia and basic numeracy skill among LINUS students. The results showed that 89.7% of the variance in students’ basic numeracy skill was accounted for by the four predictor variables (number sense, matching items, dot enumeration and number comparison) as a whole. Dyscalculic students and their non-Dyscalculic peers were also compared in terms of arithmetic abilities; and the results revealed that dyscalculic students were significantly weaker than their peers in these abilities. The findings of the present study provided implications towards developing a better understanding about the learning problems of the children with special reference to learning disability in mathematics. The findings could guide policy makers, administrators, authorities, teachers and parents to take the necessary measurements to help the children.